Short communication. Irrigation temperature effects on seedling growth and transplant quality of tomato, pepper and eggplant - Kadri Bozokalfa, M. (Spanish Journal of Agricultural Research, 2008)
During production of plug transplants, high plant density and small cell size increases seedling height. The resulting tall, weak-stemmed, plants are difficult to transplant and can be easily damaged. One technique that can prevent excessive seedling elongation is irrigation with cold water. Seedlings of tomato, pepper and eggplant were planted in cell plug trays in greenhouses and irrigated daily, in the morning, with water at different temperatures. The temperaturas tested were 3°C, 9°C and tap water (15.5-16.5°C). Irrigation with cold water reduced seedling stem height by 48-58% in tomato, 24-42% in pepper and 17-36% in eggplant. Cold water irrigation significantly affected stem diameter, number of leaves, shoot and root dry weights and leaf chlorophyll content. These results show that irrigation with cold water can effectively control plant height in plug-grown seedlings.